Impact of Financial Sector Development on Employment Generation in Nigeria - Samson, Eniekenumu Brafiya; Edewhor, Vincent (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2025)
The study investigates the impact of financial sector development on employment generation in Nigeria. The variables used in the study were financial efficiency, financial access, financial depth, and financial stability. The study applied secondary time-series data covering the period from 1980 to 2023. In the analysis, the study applied the parsimonious ECM framework and the Cointegration technique to the data. The results showed that there is a long-run relationship among the variables. The parsimonious ECM finding shows that financial access and financial depth have a positive and significant impact on employment generation, while financial stability and financial efficiency establish a positive but insignificant relationship with employment generation. In conclusion, the study showed that financial sector development impacts Nigeria's employment generation within the period. The study thus recommends that adequate financial market and financial institutions regulatory policies be introduced to improve the level of financial access, financial depth, financial efficiency, and financial stability.